Dirt - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2009)
"Feared and loathed for her poison pen and ice queen persona, Amanda Dart has made her share of enemies. Then the tables are turned. An anonymous gossipmonger is faxing Amanda's personal and private peccadilloes to anyone who can read. Desperate to save her reputation, she enlists the help of New York lawyer and private investigator Stone Barrington to learn the identity of the faxer. And everyone in the world of tabloid journalism becomes a suspect."--Page 4 of cover.